2018
DOI: 10.1186/s12872-018-0837-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of VKORC1, CYP4F2 and NQO1 gene variants on warfarin dose requirement in Han Chinese patients with catheter ablation for atrial fibrillation

Abstract: BackgroundThe anticoagulation of atrial fibrillation catheter ablation during the perioperative stage does matter and should be treated with discretion. We aimed to assess impact of three important genes participating in vitamin K cycle (i.e. VKORC1 rs9923231, CYP4F2 rs2108622 and NQO1 rs1800566) on the daily stable warfarin dose requirement in Sichuan Han Chinese patients with catheter ablation of atrial fibrillation.MethodsA total of 222 atrial fibrillation patients taking stable warfarin therapy after cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(30 reference statements)
0
17
0
1
Order By: Relevance
“…Given this evidence and the once putative role of NQO1 in vitamin K recycling, we and others have examined warfarin dose requirements by the NQO1*2 genotype with mixed results. Although no association has been identified in European or African ancestry populations, 19,40 accumulating data suggest an association in some Latino and Asian populations; although data are not entirely consistent 19,22,41,42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this evidence and the once putative role of NQO1 in vitamin K recycling, we and others have examined warfarin dose requirements by the NQO1*2 genotype with mixed results. Although no association has been identified in European or African ancestry populations, 19,40 accumulating data suggest an association in some Latino and Asian populations; although data are not entirely consistent 19,22,41,42 …”
Section: Discussionmentioning
confidence: 99%
“…Although no association has been identified in European or African ancestry populations, 19,40 accumulating data suggest an association in some Latino and Asian populations; although data are not entirely consistent. 19,22,41,42 Latinos who have varying European, African, and Native American ancestral composition share certain haplotypes with Asians, 43 in whom NQO1 associations with warfarin were documented. Our U.S. cohort included Latinos from the UAZ, who are presumably of mostly Mexican descent, as suggested by the genetic ancestry analysis, and UIC, who we previously reported were of predominantly Mexican descent, 19 with mostly European and Native American ancestry.…”
Section: Genetic Warfarin Determinants In Latinosmentioning
confidence: 99%
“…The significance of the functional promoter polymorphism, VKORC1 –1639G>A gene on the warfarin dose requirements has been studied by many researches ( Zhang et al., 2015 ; Topkara et al., 2016 ; Li et al., 2018 ). A meta-analysis including 53 studies showed that most common VKORC1 genotypes in Asian and Caucasian were -1639 AA, -1173 TT and -3730 GG, but the distribution frequency of these three genotypes in Asian was higher than that in Caucasian ( Tang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A schematic of the literature screening process is shown in Figure 1. A total of 124 articles were screened, and four articles describing 757 patients were included in the meta-analysis [9,25,30,31]. All included studies were published in English between 2007 2Cardiovascular Therapeutics and 2020.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%